Gender differences in salary and promotion for faculty in the humanities, 1977–95 - Donna K. Ginther; Kathy J. Hayes (Federal Reserve Bank of Atlanta, 2001)
This study uses data from the Survey of Doctorate Recipients to evaluate gender differences in salaries and promotion for academics in the humanities. Differences in employment outcomes by gender are evaluated using three methods: the Oaxaca decomposition is used to examine salary differentials, and binary choice models and duration analysis are used to estimate the probability of promotion to tenure. Over time, gender salary differences can largely be explained by academic rank. Substantial gender differences in promotion to tenure exist after controlling for productivity and demographic characteristics. However, the authors observe a slight decline in the gender promotion gap for the most recent cohort evaluated. On the basis of this evidence, the authors conclude that gender discrimination for academics in the humanities tends to operate through differences in promotion, which in turn affects wages.
Keywords: 330; Discrimination in employment; Labor market